Principles of igneous and metamorphic petrology - Philpotts, Anthony R.; Ague, Jay J.; Philpotts, Anthony R. (Cambridge, Cambridge University Press, 2009)
This textbook provides a basic understanding of the formative processes of igneous and metamorphic rock through quantitative applications of simple physical and chemical principles. The book encourages a deeper comprehension of the subject by explaining the petrologic principles rather than simply presenting the student with petrologic facts and terminology. Assuming knowledge of only introductory college-level courses in physics, chemistry, and calculus, it lucidly outlines mathematical derivations fully and at an elementary level, and is ideal for intermediate and advanced courses in igneous and metamorphic petrology. The end-of-chapter quantitative problem sets facilitate student learning by working through simple applications. They also introduce several widely-used thermodynamic software programs for calculating igneous and metamorphic phase equilibria and image analysis software. With over 350 illustrations, this revised edition contains valuable new material on the structure of the Earth$1 (Bs mantle and core, the properties and behavior of magmas, recent results from satellite imaging, and more.s
References 618-644p.; Index 645-667p.